Within‐person decline in pregnancy smoking is observable prior to pregnancy awareness: Evidence across two independent observational cohorts. (17th October 2022) - Massey, Suena H.; Pool, Lindsay R.; Estabrook, Ryne; Level, Rachel A.; Shisler, Shannon; Stacks, Ann M.; Neiderhiser, Jenae M.; Espy, Kimberly A.; Wakschlag, Lauren S.; Eiden, Rina D.; Allen, Norrina B.
Abstract: Decreased consumption of nicotine and other drugs during pregnancy appears to be a cross‐species phenomenon from which mechanism(s) capable of interrupting addictive processes could be elucidated. Whether pregnancy influences smoking behaviour independent of women's knowledge of the pregnancy, however, has not been considered. Using repeated measures analysis of variance (ANOVA), we estimated within‐person change in mean cigarettes/day smoked across the estimated date of conception but prior to individually reported dates of pregnancy recognition using longitudinal smoking data from two independent observational cohorts, the Growing Up Healthy (GUH, n = 271) and Midwest Infant Development Studies (MIDS, n = 145). Participants smoked an average of half a pack/day in the month immediately before conception ( M ( SD ) = 12(8.1) and 9.5(6.7) cigarettes/day in GUH and MIDS, respectively). We observed within‐person declines in smoking after conception, both before ( M GUH = −0.9; 95% CI −1.6, −0.2; p = 0.01; M MIDS = −1.1; 95% CI ‐1.9, −0.3; p = 0.01) and after ( M GUH = ‐4.8; 95% CI ‐5.5, −4.1; p < 0.001; M MIDS = −3.3; 95% CI −4.4, −2.5; p < 0.001) women were aware of having conceived, even when women who had quit and women who were planning to conceive were excluded from analyses. Pregnancy may interrupt smoking‐related processes via mechanisms not previously considered. Plausible candidates and directions for future research are discussed. Abstract : Using innovative within‐person analysis of data from two independent observational cohorts, this study estimates the protective effect of pregnancy on smoking, independent of women's knowledge of the pregnancy. Our results revealed within‐person declines in smoking after conception, both before and after women were aware of having conceived. Plausible mechanisms through which pregnancy may interrupt smoking‐related processes are discussed.